Antimicrobial and Cytotoxic Cyathane-Xylosides from Cultures of the Basidiomycete Dentipellis fragilis - Winnie Chemutai Sum; Nico Mitschke; Hedda Schrey; Kathrin Wittstein; Harald Kellner; Marc Stadler; Josphat Clement Matasyoh (MDPI AG, 2022)
In our continued search for biologically active metabolites from cultures of rare Basidiomycota species, we found eight previously undescribed cyathane-xylosides from submerged cultures of Dentipellis fragilis, which were named dentifragilins A-H. In addition, the known cyathane derivatives striatal D and laxitextine A were isolated. All compounds were characterized by high-resolution electrospray ionization mass spectrometry (HR-ESIMS) as well as by 1D and 2D nuclear magnetic resonance (NMR) spectroscopy. Several of the compounds exhibited significant activities in standardized cell-based assays for the determination of antimicrobial and cytotoxic effects. The discovery of cyathanes in the genus Dentipellis has chemotaxonomic implications, as this class of diterpenoids has already been shown to be characteristic for mycelial cultures of the related genera Hericium and Laxitextum, which are classified as Dentipellis in the family Hericiaceae.